Bio‐inspired adhesive hydrogel for biomedicine—principles and design strategies. Issue 1 (25th December 2022) - Li, Wenzhao; Yang, Xinyuan; Lai, Puxiang; Shang, Luoran
Abstract: The adhesiveness of hydrogels is urgently required in various biomedical applications such as medical patches, tissue sealants, and flexible electronic devices. However, biological tissues are often wet, soft, movable, and easily damaged. These features pose difficulties for the construction of adhesive hydrogels for medical use. In nature, organisms adhere to unique strategies, such as reversible sucker adhesion in octopuses and nontoxic and firm catechol chemistry in mussels, which provide many inspirations for medical hydrogels to overcome the above challenges. In this review, we systematically classify bioadhesion strategies into structure‐related and molecular‐related ones, which cover almost all known bioadhesion paradigms. We outline the principles of these strategies and summarize the corresponding designs of medical adhesive hydrogels inspired by them. Finally, conclusions and perspectives concerning the development of this field are provided. For the booming bio‐inspired adhesive hydrogels, this review aims to summarize and analyze the various existing theories and provide systematic guidance for future research from an innovative perspective. Abstract : General classification of biological adhesion strategies. Specifically, the corresponding examples are the hook‐like structures of cocklebur, the footpads of tree frogs, octopus suckers, catechol groups in mussel adhesives, base‐complementary pairing, snail mucus, and sandcastle worm secretions with phase behavior.